2017
DOI: 10.1002/anie.201707171
|View full text |Cite
|
Sign up to set email alerts
|

Donor–Acceptor Complex Enables Alkoxyl Radical Generation for Metal‐Free C(sp3)–C(sp3) Cleavage and Allylation/Alkenylation

Abstract: The alkoxyl radical is an essential and prevalent reactive intermediate for chemical and biological studies. Here we report the first donor-acceptor complex-enabled alkoxyl radical generation under metal-free reaction conditions induced by visible light. Hantzsch ester forms the key donor-acceptor complex with N-alkoxyl derivatives, which is elucidated by a series of spectrometry and mechanistic experiments. Selective C(sp )-C(sp ) bond cleavage and allylation/alkenylation is demonstrated for the first time us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
91
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(97 citation statements)
references
References 75 publications
5
91
1
Order By: Relevance
“…When 1 a or 2 a is added, the resonance of HE − protons at δ =3.98, 2.03 and 1.15 ppm shows remarkable downfield shifts. So an electron donor–acceptor (EDA) complex is formed between HE − and arylhalide (or arylsulfinate) in the photocatalytic process . The light on/off experiments showed that a smooth transformation under the light irradiation, but no further conversion was observed when the mixture was kept in the dark (Figure S12, Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When 1 a or 2 a is added, the resonance of HE − protons at δ =3.98, 2.03 and 1.15 ppm shows remarkable downfield shifts. So an electron donor–acceptor (EDA) complex is formed between HE − and arylhalide (or arylsulfinate) in the photocatalytic process . The light on/off experiments showed that a smooth transformation under the light irradiation, but no further conversion was observed when the mixture was kept in the dark (Figure S12, Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…So an electron donor-acceptor (EDA) complex is formed between HE À and arylhalide (or arylsulfinate) in the photocatalytic process. [24] The light on/off experiments showed that as mooth transformation under the light irradiation, but no further conversion waso bserved when the mixture was kept in the dark (Figure S12, Supporting Information). The coupling reactions were carried out at 100 8Ct or esult in the formation of 3aa in about2 5% yield with or without2 ,2'-azobis(2-methylpropionitrile) (AIBN) (Table S1,e ntries 1a nd 2, Supporting Information).…”
mentioning
confidence: 99%
“…[20] It was believed that an electron donor-acceptor (EDA) complex is formed to promote the electron transfer. [21][22] Using the similar strategy, Miyake group reported a mild, efficient, visible-light promoted protocol for the CÀS cross-coupling of thiols and aryl halides. [23] Wang group developed a new synthetic method of vinyl sulfones via light-promoted formation of EDA complex from arylsulfinic acid and biaryl isocyanide.…”
mentioning
confidence: 99%
“…The resulting highly electrophilic thiyl radical 4 rapidly undergoes a HAT event with the most hydridic α‐C−H group of the ether to generate alkoxyl radical 5 . This then cleaves the C−O bond homolytically to form a tertiary alkyl radical 6 . There are two plausible pathways, paths A and B (Scheme ) for tertiary alkyl radical trifluoromethylthiolation.…”
Section: Methodsmentioning
confidence: 99%